Internet science : INSCI 2017 International Workshops, IFIN, DATA ECONOMY, DSI, and CONVERSATIONS, Thessaloniki, Greece, November 22, 2017, Revised selected papers /: INSCI 2017 International Workshops, IFIN, DATA ECONOMY, DSI, and CONVERSATIONS, Thessaloniki, Greece, November 22, 2017, Revised selected papers. (2018) - Unknown
No abstract available